Substituted nickel ferrite coated MWCNT/PVDF based epoxy nanocomposite for microwave absorption. Issue 20 (15th October 2022) - Siddiki, Salim H.; Das, Sukanta; Verma, Kartikey; Dashairya, Love; Das, Sushrut; Thakur, Vijay Kumar; Nayak, G.C.
Abstract: Metal-substituted spinel ferrite-based microwave absorbing materials (MAMs) are attracting significant attention due to their varied soft magnetic behaviour, and ease of synthesis. This work established the efficiency of Cd 2+ substituted nickel ferrite coated MWCNT (with varied MWCNT loading) for X-band microwave absorption, in the presence of PVDF. The substituted ferrite was prepared with a facile solvothermal process. X-ray diffraction and vibrating sample magnetometer analysis confirmed the spinel structure of substituted ferrites and tuned magnetic behaviour of Cd 2+ substituted ferrite structure, respectively. FESEM revealed a uniform coating of substituted ferrite on MWCNT and XPS confirmed Cd 2+ substitution. Hybrid nanocomposites of ferrite coated MWCNT with PVDF, in the epoxy matrix, revealed superior microwave absorption for NiF-150_10 PV and CdNiF-150_10 PV with an absorber thickness of 3 mm in the X band. The absorption bandwidth with the RL below −10 dB reached 3.9 GHz and 3.6 GHz for NiF-150_10 PV and CdNiF-150_10 PV, respectively. The microwave absorption mechanism was discussed in detail. The developed NiF-150_10 PV and CdNiF-150_10 PV composites can be used as lightweight, low thickness microwave absorbers in the defense and telecommunication industries. Graphical abstract: Image 1